Pengoptimalan Penggunaan dan Fungsi ChatGPT Pada Anak Muda Gereja St.Petrus Palembang - Michael; Andreas Danny Agus W; Muhammad Rizky Pribadi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This study discusses the implementation of community service activities for young people at St. Petrus Palembang by using ChatGPT technology as a tool to introduce and train its use. This training aims to understand the concept of ChatGPT and improve skills in using this technology effectively and efficiently. The method used in this activity is presentation and hands-on practice. The results of this training show that the use of ChatGPT can improve the quality of learning for participants through interesting and interactive interactions. Participants can easily understand technology concepts through interaction with ChatGPT, which provides fast and accurate responses and explanations. The advice given is to carry out routine training programs in Sunday Schools to strengthen the use of technology in learning and to develop various types of content that can be accessed through ChatGPT to provide a deeper understanding of technology through interaction with digital technology.